Development of maize cob-based biochar filter for water purification - Oluk, Isaac; Nagawa, Christine Betty; Banadda, Noble; Tumutegyereize, Peter; Achaw Owusu, Prosper (Water and Environment Journal, 2021)
The study aimed at biochar production from maize cob and its performance in improving water physiochemical attributes. Three feedstock masses (2, 2.5, 3 kg) were used for biochar production. Nine treatment combinations of T1L1, T1L2, T1L3, T2L1, T2L2, T2L3, T3L1, T3L2 and T3L3 in triplicate were used for biochar performance. Biochar yield of 50% was averagely achieved at slow pyrolysis conditions (300 to 600°C) and 120 min residence time. Biochar had 4.13% moisture content, 6.86% ash, 17.70% volatile matter, 71.28% fixed carbon, and a pH of 10.27. Odour, colour, and total hardness of the wastewater improved after filtration using biochar to acceptable levels for potable water use. Total hardness reduced by 51.9% in T2L2 and 44.4% in T3L2. Findings front maize cob biochar as a purification technology for domestic potable water use. There is need for maize cob biochar performance on heavy metals and when it is sandwiched with other materials.
Keywords: Biochar; Maize cobs; Pyrolysis; Water filter; Water quality